Stability and thermal analysis of MWCNT-thermal oil-based nanofluids - Ilyas, S.U. (Elsevier B.V., 2017)
Carbon nanotubes (CNTs) have gained much attention due to excellent thermal properties. Numerous studies have reported the incremental thermal conductivity of CNT-based nanofluids. However, limited studies are available on the complete thermal and viscous transport effects in oil-based nanofluids. Multi-wall carbon nanotubes (MWCNTs)-thermal oil-based nanofluids are prepared using two-step method. The high stability is achieved using mechanical mixing technique (ultrasonication) only. Surfactant-free nanofluids are prepared in various concentrations of 0–1 wt.. Dispersion behaviour of nanofluids is investigated to ensure high stability of nanofluids using different characterizations. The effective thermophysical properties such as density, viscosity, thermal conductivity, and specific heat capacity are experimentally investigated at different temperature ranges and nanoparticle concentrations. The experimental findings of the present work are compared with the theoretical models and good agreement is observed for effective density of nanofluids. However, other thermophysical properties show a significant deviation with the conventional models. The coefficient of thermal expansion is calculated for oil-based nanofluids. Correlations are developed for thermophysical properties of nanofluids. Thermogravimetric analysis (TGA) is carried out to understand the effect of nanotubes on the life-cycle and the degradation temperature of thermal oil. © 2017 Elsevier B.V.